Does Fiscal Decentralization Impact Environmental Quality in Indonesia? - Sulistyo, Indra; Priyagus, Priyagus; Lestari , Diana (Universitas Bangka Belitung, 2026)
Purpose: In realizing the need for environmental governance, this study examines the effect of fiscal decentralization on Environmental Quality Index (IKLH) through Green Budgeting as mediation and educational-level moderation as proxy social supervision. Design/Methodology/Approach: Using a balanced panel dataset of 34 Indonesian provinces for the period 2018 to 2024, the study employs Two-Stage Least Squares (TSLS) with Fixed Effects. This approach systematically identifies and accounts for endogeneity bias between fiscal capacity, budgetary allocations, and ecological outcomes. Key Findings: The first-stage estimation indicates that the Flypaper Effect and the Resource Curse are rigid; indeed, none of the central transfers (DAU, DAK, DBH) have an effect on encouraging Green Budgeting. As such, Local Own-Source Revenue (PAD) is established as the driver of ecological innovation. A crucial conditional moderation is highlighted in the second stage: Green Budgeting (GB) alone has no effect on, or improves, IKLH, but when combined with higher education, it acts effectively and, by any means, becomes an important driver of environmental quality. Originality/value: This research challenges the widely held notion that fiscal decentralization improves local environments. It lends empirical support to the argument that, in the absence of rigorous scrutiny from a well-informed citizenry (demand-side social control), government financial interventions (supply-side) will continue to spur inefficiencies. Practical/Policy implications: The reform of revenue-sharing schemes into Ecological Fiscal Transfers (EFT) should be treated as an emergency solution by the central government, whereas local governments must implement transparency in the execution of environmental budget to enforce community social control.